STUDYING FOREIGN EXPERIENCE OF RISK INSURANCE OF PRIVATE AND SMALL ENTREPRENEURSHIP - Daniyarovna, Karimova Kamila (International Journal of Psychosocial Rehabilitation, 2020)
In the economy of any country characterized by a market management system, small and medium-sized businesses play a significant role. In transformational economies, the role of small and medium-sized businesses is indispensable in solving the most pressing economic and social problems. Not requiring significant costs from the state, small and medium-sized businesses, as a phenomenon, stabilize the social situation in the country, solving problems associated with social tension and employment